2021
DOI: 10.24289/ijsser.838429
|View full text |Cite
|
Sign up to set email alerts
|

General perceptions and information sources of people in Turkey in the process of Covid-19 outbreak

Abstract: This study is an attempt to define and explain the main information sources people applied to access more information during the Covid-19 pandemic process. Based on the findings of the field study, the study also aims to reveal the general perceptions of Turkish people towards the outbreak. According to the findings of the survey, conducted on 6021 people over 18 years old in 26 provinces in Turkey, people living in these provinces rely on information provided by the official authorities mostly and their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, Turkish leftist media outlets criticized AKP government as incapable due to the mismanagement of COVID-19-related health policies. Recent research, however, has revealed that official government statements are increasingly viewed as the most reliable sources of information during the COVID-19 period ( Avsar et al, 2021 ). Furthermore, COVID-19-related content on traditional media outlets in Turkey had better engagement rates by partisan social media followers ( Kirdemir, 2020 ), despite the growing popularity of social media and government crackdowns on independent and left-leaning journalists ( Amnesty International, 2020 ).…”
Section: Political Polarization In the Akp Eramentioning
confidence: 99%
“…On the contrary, Turkish leftist media outlets criticized AKP government as incapable due to the mismanagement of COVID-19-related health policies. Recent research, however, has revealed that official government statements are increasingly viewed as the most reliable sources of information during the COVID-19 period ( Avsar et al, 2021 ). Furthermore, COVID-19-related content on traditional media outlets in Turkey had better engagement rates by partisan social media followers ( Kirdemir, 2020 ), despite the growing popularity of social media and government crackdowns on independent and left-leaning journalists ( Amnesty International, 2020 ).…”
Section: Political Polarization In the Akp Eramentioning
confidence: 99%